2023
DOI: 10.3390/molecules28227678
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of New Polyamines Conjugated with Oxygen-Containing Aromatic Functional Groups

Mario Inclán,
Neus Torres Hernández,
Alejandro Martínez Serra
et al.

Abstract: Antibiotic resistance is now a first-order health problem, which makes the development of new families of antimicrobials imperative. These compounds should ideally be inexpensive, readily available, highly active, and non-toxic. Here, we present the results of our investigation regarding the antimicrobial activity of a series of natural and synthetic polyamines with different architectures (linear, tripodal, and macrocyclic) and their derivatives with the oxygen-containing aromatic functional groups 1,3-benzod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In this study, we proposed selecting BAs as reagents for synthesizing new SBs. It should be noted that the antibacterial properties of BAs are discussed in the literature [20][21][22]. The SBs obtained and the reagents (BAs, 2-FBS, and 3-FBS) were individually tested as an antibacterial agent against E. coli and S. aureus.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we proposed selecting BAs as reagents for synthesizing new SBs. It should be noted that the antibacterial properties of BAs are discussed in the literature [20][21][22]. The SBs obtained and the reagents (BAs, 2-FBS, and 3-FBS) were individually tested as an antibacterial agent against E. coli and S. aureus.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Moreover, the multiple activities induced by polyamines due to their interaction with different biological targets support the proposal of the polyamine skeleton as a universal model for further modification. According to Inclán et al [20], polyamine research has become an essential field for drug development. Their potential application has been studied as anticancer and antiproliferative agents, agonist-antagonist receptor ligands, or antiparasitic compounds.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The modular polyamine backbone allowed for preparing long linear derivatives with a broad spectrum of antimicrobial activity against multidrug-resistant bacteria [ 86 ]. Polyamines with diverse molecular architecture (linear, tripodal, and macrocyclic) and their derivatives with aromatic functional groups, such as 1,3-benzodioxol, ortho- and -para phenol, or 2,3-dihydrobenzofuran, indicated that the topology of the polyamine scaffold is essential for the antimicrobial activity of conjugates [ 87 ]. From the hemocytes of the tarantula spider Acanthoscurria gomesiana , the bis-acyl polyamine spermidine with antimicrobial and immunomodulatory activity was characterized, and its mechanism of action has been investigated in molecular detail [ 88 , 89 ].…”
Section: Spider and Wasp Acylpolyamines As Versatile Pharmacological ...mentioning
confidence: 99%